As características estruturais e organizacionais das UBS influenciam as taxas de internações de crianças por condições sensíveis à atenção primária? - LISBOA, Livia Anniele Sousa (2015)
Introduction: Among the Primary Care Sensitive Conditions (ACSC) in children under five, asthma, diarrhea and pneumonia are the leading causes of hospitalization. Several aspects of primary care can influence hospitalizations, however, doubts remain about the role of the structural Basic Health Units (BHU). Objective: To analyze the association between structural and organizational characteristics of BHU and hospitalizations for ACSC in the 27 Brazilian capitals. Method: analytical ecological study, using data for the municipalities of Brazilian states, the analytical units were the federal capital. The databases used were the National Programme for Improving Access and Quality of Primary Care, the Hospital Information System of SUS, Information System of Primary Care and annual population surveys conducted by the Brazilian Institute of Geography and Statistics, the United Nations Development Programme and National Research by Household Sample and collected in DATASUS sites Associations were estimated by relative risk (RR) in Poisson regression analysis with hierarchical approach, with the dependent variable the number of pediatric hospitalizations for asthma, diarrhea and pneumonia as independent variables and the organizational and structural features of BHU, adjusted for the demographic, socioeconomic and municipal health. Results: municipalities had low fitness of the BHU structure for the care of children in primary care. In the final model, the availability of equipment (p = 0.002; RR: 0,98), vaccines (p = 0.001; RR: 0,98) and the overall adequacy of BHU's physical structure (p <0.001; RR: 0, 98) were associated with hospitalization as a protective factor, while the number of doctors in BHU (p = 0.040; RR: 1,39) was associated as a risk factor. Conclusion: adequate supply of primary care, specifically the structural characteristics, is associated with decreased hospital admissions, while the largest medical number has not impacted the promotion and pediatric prevention.